Arterial wall fibrosis in Takayasu arteritis and its potential for therapeutic modulation - Misra, Durga Prasanna; Singh, Kritika; Sharma, Aman; Agarwal, Vikas (Frontiers in Immunology, 2023)
Arterial wall damage in Takayasu arteritis (TAK) can progress despite immunosuppressive therapy. Vascular fibrosis is more prominent in TAK than in Giant Cell Arteritis (GCA). The inflamed arterial wall in TAK is infiltrated by M1 macrophages [which secrete interleukin-6 (IL-6)] which transition to M2 macrophages once the inflammation settles. M2 macrophages secrete transforming growth factor beta (TGF-𝞫) and glycoprotein non-metastatic melanoma protein B (GPNMB), both of which can activate fibroblasts in the arterial wall adventitia. Mast cells in the arterial wall of TAK also activate resting adventitial fibroblasts. Th17 lymphocytes play a role in both TAK and GCA. Sub-populations of Th17 lymphocytes, Th17.1 lymphocytes [which secrete interferon gamma (IFN-) in addition to interleukin-17 (IL-17)] and programmed cell death 1 (PD1)-expressing Th17 (which secrete TGF-𝞫), have been described in TAK but not in GCA. IL-6 and IL-17 also drive fibroblast activation in the arterial wall. The Th17 and Th1 lymphocytes in TAK demonstrate an activation of mammalian target organ of rapamycin 1 (mTORC1) driven by Notch-1 upregulation. A recent study reported that the enhanced liver fibrosis score (derived from serum hyaluronic acid, tissue inhibitor of metalloproteinase 1, and pro-collagen III amino-terminal pro-peptide) had a moderate-to-strong correlation with clinically-assessed and angiographically-assessed vascular damage. In vitro experiments suggest the potential to target arterial wall fibrosis in TAK with leflunomide, tofacitinib, baricitinib, or mTORC1 inhibitors. Since arterial wall inflammation is followed by fibrosis, a strategy of combining immunosuppressive agents with drugs which have an antifibrotic effect merits exploration in future clinical trials of TAK.